2018
DOI: 10.1007/s00300-018-2275-8
|View full text |Cite
|
Sign up to set email alerts
|

The genus Cyamiocardium Soot-Ryen, 1951 (Bivalvia: Cyamiidae) in sub-Antarctic and Antarctic waters

Abstract: For more than 50 years the genus Cyamiocardium was regarded as represented by three species: Cyamiocardium denticulatum (with Cyamiocardium rotundatum as a synonym), Cyamiocardium dahli, and Cyamiocardium crassilabrum. However, in the last years, the latter was removed from Cyamiocardium, alternatively being placed into Perrierina. All these species were mainly based on the general shell morphology of a reduced number of specimens, with scarce (or no) information on their anatomy and reproductive traits. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Some important results obtained from the study of the samples taken during the Argentinean research cruises between 2013 and 2018 are the inventories of ascidians (Taverna et al, ), Asteroidea (Fraysse, Calcagno, & Pérez, ), brachiopods (Gordillo, Bayer, de Aranzamendi, Taverna, & Morán, ), molluscs (Di Luca & Zelaya, ), and polychaetes (Bremec et al, ), and the distribution and reproduction of some fishes have been also reported by García Alonso, Brown, Martín, Pájaro, and Capitanio (). Several new species have also been discovered in this area (Schejter, Bertolino, & Calcinai, ; Güller & Zelaya, ; Urcola & Zelaya, ; López Gappa, Liuzzi, & Zelaya, ), and many more are undergoing the description process. In the coming years, more results and data will be published and will be available in order to analyse and describe the complete picture of this complex ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…Some important results obtained from the study of the samples taken during the Argentinean research cruises between 2013 and 2018 are the inventories of ascidians (Taverna et al, ), Asteroidea (Fraysse, Calcagno, & Pérez, ), brachiopods (Gordillo, Bayer, de Aranzamendi, Taverna, & Morán, ), molluscs (Di Luca & Zelaya, ), and polychaetes (Bremec et al, ), and the distribution and reproduction of some fishes have been also reported by García Alonso, Brown, Martín, Pájaro, and Capitanio (). Several new species have also been discovered in this area (Schejter, Bertolino, & Calcinai, ; Güller & Zelaya, ; Urcola & Zelaya, ; López Gappa, Liuzzi, & Zelaya, ), and many more are undergoing the description process. In the coming years, more results and data will be published and will be available in order to analyse and describe the complete picture of this complex ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exhaustive species inventories, descriptions of new species, new records of distribution, and studies on reproductive biology and biogeography have been recently published on the fauna from Burdwood Bank (Güller and Zelaya 2017; Penchaszadeh et al 2017Penchaszadeh et al , 2019Schejter et al 2017a;Fraysse et al 2018Fraysse et al , 2020García Alonso et al 2018;López Gappa et al 2018;Taverna et al 2018;Urcola and Zelaya 2018;Bremec et al 2019;Di Luca and Zelaya 2019;Gordillo et al 2019;Teso and Penchaszadeh 2019;Pérez-Barros et al 2020;Roccatagliata 2020;among others).…”
Section: Introductionmentioning
confidence: 99%